PENANAMAN MANGROVE UNTUK MENGATASI MASALAH BANJIR PADA KAWASAN PESISIR YANG ADA DI DAERAH CAMPALAGIAN - M. Sahib Saleh; Fadel Mulia; Fitra Abu Khaer; Muhammad Syahrul Saleh; Syahruddin, Syahruddin (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
This service activity aims to find out, study, and describe problems or needs in vocational high schools that have not been met. This study used a descriptive qualitative method because in this study it produced data that described in detail the conditions in the field and the source of the data was obtained from interviews with school principals regarding problems or things needed by the school and based on observations. SMKN Campalagian is a vocational high school located in Polewali Mandar Regency. SMKN Campalagian is a school that is close to the beach area. Based on the results of observations, UNM KKN-PPL Students Batch XXV planted mangrove trees as a project to strengthen the profile of Pancasila students towards students with an independent learning curriculum. This planting is a form or movement of loving the environment by planting trees and reducing plastic waste. UNM KKN-PPL students Batch XXV brought the theme, Sustainable Lifestyle, meaning that coastal areas are maintained by their ecosystem and can reduce the risk of flooding or natural disasters.